1992
DOI: 10.1152/jn.1992.67.4.1009
|View full text |Cite
|
Sign up to set email alerts
|

Isolated NMDA receptor-mediated synaptic responses express both LTP and LTD

Abstract: 1. The possibility of use-dependent, long-lasting modifications of pharmacologically isolated N-methyl-D-aspartate (NMDA) receptor-mediated synaptic transmission was examined by intracellular recordings from granule cells of the hippocampal dentate gyrus in vitro. In the presence of the non-NMDA receptor antagonist 6-cyano-7-nitroquinaxaline-2,3-dione (CNQX, 10 microM) robust, long-term potentiation (LTP) of NMDA receptor-mediated synaptic potentials was induced by brief, high (50 Hz) and lower (10 Hz) frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(64 citation statements)
references
References 0 publications
2
62
0
Order By: Relevance
“…Our laboratory has previously shown that pharmacologically isolated NMDARs can express LTP in the presence of reduced concentrations of Mg 2ϩ , or at depolarizing potentials in the presence of normal Mg 2ϩ (Xie et al, 1992). In the present study, we further test the possibility that NMDARs express LTP in the presence of normal Mg 2ϩ and in response to physiological patterns of afferent stimulation.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Our laboratory has previously shown that pharmacologically isolated NMDARs can express LTP in the presence of reduced concentrations of Mg 2ϩ , or at depolarizing potentials in the presence of normal Mg 2ϩ (Xie et al, 1992). In the present study, we further test the possibility that NMDARs express LTP in the presence of normal Mg 2ϩ and in response to physiological patterns of afferent stimulation.…”
Section: Introductionmentioning
confidence: 72%
“…Hippocampal slices were prepared from New Zealand white rabbits as by Xie et al (1992). Briefly, transverse hippocampal slices (500-m thick) were cut with a vibratome and were incubated in medium consisting of (in mM): NaCl, 126; KCl, 3; NaH 2 PO 4 , 1.25; NaHCO 3 , 26; glucose, 10; CaCl 2 , 2; MgSO 4 , 2, aerated with 95% O 2 /5% CO 2 .…”
Section: Slice Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that long-term potentiation (LTP) and long-term depression (LTD) of NMDAR transmission can be induced by increased presynaptic activity. In particular, high-frequency stimulation (HFS) rapidly induces LTP of NMDAR-EPSPs/EPSCs in the hippocampal dentate gyrus (O'Connor et al, 1994(O'Connor et al, , 1995Harney et al, 2006), CA1 (Bashir et al, 1991;Berretta et al, 1991;Asztely et al, 1992;Xie et al, 1992;Clark and Collingridge, 1995;Kullmann et al, 1996;Jia et al, 1998;Grosshans et al, 2002;Kotecha et al, 2003;Lozovaya et al, 2004), and CA3 (Kwon and Castillo, 2008;Rebola et al, 2008) (for review, see Lau and Zukin, 2007). LTD of NMDAR-EPSCs can also be induced by low-frequency stimulation (Morishita et al, 2005) or by HFS under conditions of relatively high intracellular Ca 2ϩ buffering (Harney et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In DG granule cells, the enhancement of depolarization by TEA was much weaker compared with that in CA1 and, as a consequence, the Ca 2ϩ influx was much reduced. It has been established that low levels of Ca 2ϩ influx are associated with LTD, as we observed for the DG (Xie et al, 1992). Our experiments and simulations were carried out on CA1 pyramidal cells and DG granule cells; studies of CA3 pyramidal cell were not included in our analyses.…”
mentioning
confidence: 99%